Associations of heat with diseases and specific symptoms in Flanders, Belgium: An 8-year retrospective study of general practitioner registration data - Endale Alemayehu Ali; Bianca Cox; Karen Van de Vel; Els Verachtert; Bert Vaes; Simon Gabriel Beerten; Elisa Duarte; Charlotte Scheerens; Raf Aerts; Gijs Van Pottelbergh (Environment International)
Introduction: Global temperature rise has become a major health concern. Most previous studies on the impact of heat on morbidity have used hospital data. Objective: This study aimed to quantify the association between ambient temperature and a variety of potentially heat-related medical conditions and symptoms using general practitioner (GP) data, in Flanders, Belgium. Methods: We used eight years (2012–2019) of aggregated data of daily GP visits during the Belgian summer period (May-September). A distributed lag nonlinear model (DLNM) with time-stratified conditional quasi-Poisson regression was used to account for the non-linear and delayed effect of temperature indicators (minimum, mean and maximum). We controlled for potential confounders such as particulate matter, humidity, and ozone. Results: The overall (lag0-14) association between heat and most of the outcomes was J-shaped, with an increased risk of disease observed at higher temperatures. The associations were more pronounced using the minimum temperatures indicator. Comparing the 99th (20 °C) to the minimum morbidity temperature (MMT) of the minimum temperature distribution during summer, the relative risk (RR) was significantly higher for heat-related general symptoms (RR = 1.30 [95 % CI: 1.07, 1.57]), otitis externa (RR = 4.87 [95 % CI:2.98, 7.98]), general heart problems (RR = 2.43 [95 % CI: 1.33, 4.42]), venous problems (RR = 2.48 [95 % CI:1.55, 3.96]), respiratory complaints (RR = 1.97 [95 % CI: 1.25, 3.09]), skin problems (RR = 3.26 [95 % CI: 2.51, 4.25]), and urinary infections (RR = 1.37 [95 % CI: 1.11, 1.69]). However, we did not find evidence for heat-related increases in gastrointestinal problems, cerebrovascular events, cardiovascular events, arrhythmia, mental health problems, upper respiratory problems and lower respiratory problems. An increased risk of allergy was observed when the minimum temperature reached 17.8 °C (RR = 1.50 [95 % CI: 1.23, 1.83]). Acute effects of heat were observed (largest effects at the first few lags). Summary: Our findings indicated that the occurrence of certain symptoms and illnesses during summer season is associated to high temperature or environmental exposures that are augmented by elevated temperatures. Overall, unlike hospitalization data, GP visits data provide broader population coverage, revealing a more accurate representation of heat-health association.